Preferensi Kumbang Beras (Sitophilus oryzae L.) pada Tujuh Varietas Jagung - Rahman, Moch Rifki Andika; Pramono, Sudi; Solikhin, Solikhin; Swibawa, I Gede (Universitas Lampung, 2024)
The rice weevil (Sitophilus oryzae L.) is a primary pest of rice but also has the capacity to infest other grain commodities, such as maize.The objective of this study is to determine the preference of rice weevils to seven different maize varieties.The research was conducted at the Plant Pest Science Laboratory, Faculty of Agriculture, University of Lampung, from March to August 2024.The preference test was assessed using the Free Choice Test Method (FCTM). The experiment involved the placement of 30 g of each maize variety in separate treatments, with 30 pairs of S. oryzae positioned at the center of the cage. This design ensured equal opportunity for the weevils to select any of the maize varieties. The preference test spanned seven days, after which each maize variety was subjected to an incubation period of one month. The observed variables included the preference or number of rice weevil imago (both male and female), the number of first-generation offspring, median development time, sensitivity index, percentage of damage, and weight loss of maize.The research results indicated that S. oryzae exhibited the highest preference for the Kristal Madura maize variety compared to six other maize varieties. The highest number of male and female imago, as well as first-generation offspring, was observed in the Kristal Madura variety.The susceptibility index of the Kristal Madura variety was the highest, making it the most vulnerable variety.The highest percentage of weight loss was observed in the Kristal Madura and Kretek Madura varieties.